Structural investigation and intracellular trafficking of a novel multicomposite cationic solid lipid nanoparticle platform as a pDNA carrier. (November 2011) - Vighi, Eleonora; Leo, Eliana; Montanari, Monica; Mucci, Adele; Hanuskova, Miriam; Iannuccelli, Valentina
Background: The ability to efficiently cross cellular barriers and accomplish high-level transgene expression is a critical challenge to broad application of nonviral vectors, such as cationic solid lipid nanoparticles (SLN).Aims: This study aims to design and characterize in vitro multicomposite SLN as a novel platform for pDNA delivery.Results/Discussion: The distribution of each component (stearic acid, stearylamine, phosphatidylcholine, cholesterol, protamine and Pluronic F68) in the SLN matrix was studied by electron spectroscopy for chemical analysis and NMR in order to establish its influence on SLN cytotoxicity and transfection efficiency. Multicomposite SLN mediated the expression of enhanced green fluorescent protein in a way comparable with the positive control, but inducing a lower cytotoxicity. Moreover, the carrier exhibited the ability to enter the nucleoli, probably as a result of the synergic action of the nuclear localization signal of protamine and the flexibility of the lipid matrix owing to the phosphatidylcholine.Conclusion: The multicomposite SLN showed good transfection efficiency and negligible cytotoxicity, both crucial factors for an efficient gene-delivery system. Considering the fact that nucleoli have emerged in recent years as important targets in many fields, this novel carrier could have significant future therapy involvements whenever there is a requirement to overcome subcellular barriers. However, further work needs to be carried out in order to fully characterize the formulation, to elucidate where alternative colloidal structures might exist and play a role in obtaining the results presented.